A composite positive electrode material and its preparation method and application

By adopting a composite positive electrode material with a core-shell structure, a lithium-rich manganese-based material doped with lithium-ferrophosphate as the core is used to coat the lithium-ferrophosphate-doped lithium-ferrophosphate as the coating layer, the lithium-ferrophosphate-rich manganese-manganese-manganese-ferrophosphate is solved at a high voltage. The problem of poor stability and safety hazards has achieved efficient electrochemical performance and safety performance improvement, while simplifying the preparation process and reducing costs.

CN118970020BActive Publication Date: 2025-02-07河北九丛科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411441105.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-07
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have poor stability at high voltages and are easily catalyzed with the electrolyte, resulting in rapid attenuation of battery performance and safety hazards. At the same time, the improved composite materials have complex structure, long process and high cost.

Method used

The composite positive electrode material adopts a core-shell structure, the core is a lithium-rich manganese-based material doped with carbon coated lithium manganese phosphate, and the coating layer is lithium manganese phosphate. The lithium ion transmission channel is improved through the carbon coated material and through the phosphoric acid A dense cladding of lithium manganese iron manganese barriers contact between lithium-rich manganese-based materials and electrolytes.

Benefits of technology

The discharge specific capacity and cycle stability of composite positive electrode materials are significantly improved, the safety performance of the battery is enhanced, the preparation process is simplified and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118970020B_ABST
    Figure CN118970020B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of battery material technology, and specifically to a composite positive electrode material, a preparation method and application thereof. The composite positive electrode material is a core-shell structure, including a core and a coating layer coated on the surface of the core; wherein the core is a carbon-coated lithium iron manganese phosphate-doped lithium-rich manganese-based material; and the coating layer is lithium iron manganese phosphate. The composite positive electrode material provided by the present invention not only greatly improves the discharge specific capacity and cycle stability of the lithium-rich manganese-based material, but also effectively blocks the contact between the lithium-rich manganese-based material and the electrolyte, greatly improving the safety performance of the positive electrode material system. The technical solution of the present invention effectively solves the problems in the prior art that the lithium-rich manganese-based material catalyzes the decomposition of the electrolyte, causing rapid attenuation of battery performance, potential safety hazards, and the improved composite lithium-rich manganese-based material has a complex structure, a long process and high cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a composite positive electrode material and a preparation method and application thereof. Background Art

[0002] With the development of industries such as electric vehicles and drones, the specific energy requirements for battery systems are getting higher and higher. At present, the industry generally believes that solid-state batteries are the main direction of future high-specific-energy battery technology development. Solid-state batteries can increase the specific energy of battery systems to 400-500Wh / kg, and battery systems using metal lithium negative electrodes even have the potential to reach 1000Wh / kg. The positive electrode material accounts for about 1 / 3 of the battery weight, and the capacity of the positive electrode material has also become an important issue restricting battery development.

[0003] The lithium-rich manganese-based positive electrode is a material that has been studied more in recent years. It has a gram capacity of more than 300mAh / g, which is superior to the current lithium iron phosphate (140mAh / g) and high nickel ternary (200mAh / g). It is the positive electrode system with the highest gram capacity at present and is also the preferred positive electrode system for solid batteries. The lithium-rich positive electrode material xLi2MnO3·(1−x)LiMO2 used in lithium-ion batteries is a solid solution formed by layered materials Li2MnO3 and LiMO2 in different proportions, which can also be written as Li 1+x M 1-x O2, M can be elements such as Co, Ni, Fe, and Mn. However, traditional lithium-rich manganese-based materials can only exert high capacity in high-voltage systems, and they are very serious in catalytic decomposition of electrolytes, causing rapid degradation of battery system performance. At the same time, lithium-rich manganese-based materials will also produce oxygen under conditions such as short circuits and punctures, posing a safety hazard to the battery. To this end, many researchers have made technical improvements.

[0004] The prior art reports methods for improving the initial efficiency, cycle stability, thermal stability, rate performance and capacity of lithium-rich manganese-based materials through a variety of technical means. Among them, there are reports that address the problem of poor stability of positive electrode materials under high voltages, and provide a modification method including active materials and a solid electrolyte layer coated on the surface thereof, which effectively improves the electrochemical window of the positive electrode material, inhibits irreversible changes in the lattice, and improves stability under high voltage conditions. There are also reports that provide a doping technology to solve the problem of capacity attenuation caused by irreversible structural transformation of lithium-rich manganese-based materials during cycling, and stabilize the crystal structure.

[0005] Lithium iron manganese phosphate is also a new generation of positive electrode material. It has the safety characteristics of lithium iron phosphate and increases the energy density of the battery by 15%-20% by increasing the voltage, thereby improving the energy density and low temperature performance of the battery. However, lithium iron manganese phosphate has a specific capacity of only about 150mAh / g, which is not suitable for systems with higher specific energy requirements. However, its composite with high-gram capacity positive electrode materials has great advantages, such as improving safety performance, improving gas production problems, and extending cycle life. At present, there are reports proposing a technical solution for coating lithium iron manganese phosphate with lithium-rich manganese-based materials to form a structure of lithium iron manganese phosphate / lithium-rich manganese-based / carbon coating layer, which can effectively improve the lithium ion and electron conductivity of the composite positive electrode material and the cycle life at room temperature and high temperature. However, the overall material structure is relatively complex, the process is relatively long, and the crystal structure of the lithium-rich manganese-based material needs to be limited, resulting in a high preparation cost. Based on this, the development of a lithium-rich manganese-based positive electrode material with excellent performance, simple preparation and low cost has a driving significance for the preparation of battery materials. Summary of the invention

[0006] In view of the problems in the prior art that the lithium-rich manganese-based materials catalytically decompose the electrolyte, causing rapid attenuation of battery performance, potential safety hazards, and the complex structure, long process and high cost of the improved composite lithium-rich manganese-based materials, the present invention provides a composite positive electrode material and its preparation method and application. The composite positive electrode material is a core-shell structure, the core is a carbon-coated lithium iron manganese phosphate doped lithium-rich manganese-based material, and the coating layer material coated on the surface of the core material is lithium iron manganese phosphate. The present invention uses carbon-coated lithium iron manganese phosphate with higher safety as a dopant to dope and modify the lithium-rich manganese-based material, which greatly improves the discharge specific capacity and cycle stability of the lithium-rich manganese-based material; the coating layer effectively blocks the contact between the lithium-rich manganese-based material and the electrolyte, inhibits the catalytic decomposition of the electrolyte, and greatly improves the safety performance of the positive electrode material system. More importantly, the method for preparing the composite positive electrode material of the present invention is simple and low-cost, providing a new idea for the research of positive electrode materials.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The first aspect of the present invention provides a composite positive electrode material, which is a core-shell structure, including an inner core and a coating layer coated on the surface of the inner core; wherein the inner core is a carbon-coated lithium manganese iron phosphate-doped lithium-rich manganese-based material; and the coating layer is lithium manganese iron phosphate.

[0009] Compared with the prior art, the present invention adopts carbon-coated lithium iron manganese phosphate with better safety and higher conductivity as a dopant to dope and modify the lithium-rich manganese-based material, which can form more lithium ion transmission channels inside the lithium-rich manganese-based material, thereby greatly improving the discharge specific capacity and cycle stability of the composite positive electrode material. In addition, the present invention also performs surface coating on the lithium-rich manganese-based material doped with carbon-coated lithium iron manganese phosphate, and forms a highly stable interface layer on its surface by using the dense coating of lithium iron manganese phosphate, effectively avoiding the contact between the lithium-rich manganese-based material and the electrolyte, and inhibiting the metal elements contained in the lithium-rich manganese-based material from catalyzing the decomposition of the electrolyte, thereby effectively solving the problem of electrolyte catalytic gas production caused by the lithium-rich manganese-based material and the battery performance attenuation and expansion bulging caused by the lithium-rich manganese-based material, and greatly improving the safety performance of the battery. The composite positive electrode material of the present invention combines lithium iron manganese phosphate and lithium-rich manganese-based materials with a simple core-shell structure, and utilizes the synergistic effect of the two, which not only makes up for the defects of traditional lithium-rich manganese-based materials, but also greatly improves the electrochemical performance of the positive electrode material. The present invention effectively solves the problem in the prior art that lithium-rich manganese-based materials catalyze decomposition of electrolytes, causing rapid attenuation of battery performance and potential safety hazards, and provides more ideas for the research of positive electrode materials.

[0010] Preferably, the method for preparing the carbon-coated lithium manganese iron phosphate material comprises the following steps:

[0011] S1. Immersing lithium manganese iron phosphate in a saturated glucose solution, separating the solid and the liquid, and drying to obtain a pretreated sample;

[0012] S2. In an inert atmosphere, sintering the pretreated sample at 580° C.-620° C. to obtain the carbon-coated lithium manganese iron phosphate.

[0013] Further preferably, in S1, the mass volume ratio of the lithium manganese iron phosphate to the saturated glucose solution is 1g:4mL-1g:6mL.

[0014] Further preferably, in S2, the temperature is increased to 580°C-620°C at a heating rate of 8°C / min-12°C / min.

[0015] Further preferably, in S2, the sintering time is 2.5h-4h.

[0016] Preferably, the composite positive electrode material comprises the following components in percentage by mass: 1%-3% of carbon-coated lithium iron manganese phosphate, 0.5%-5% of lithium iron manganese phosphate and the remainder of lithium-rich manganese-based material.

[0017] Preferably, the particle size of the carbon-coated lithium manganese iron phosphate is 0.2 μm-1.2 μm.

[0018] Preferably, the chemical formula of the lithium-rich manganese-based material is Lia Mn b M c O2, wherein a+b+c=2, 1<a≤1.2, 0.5<b≤0.6, 0.1<c≤0.3; M is any one or more of Ni, Co or Fe.

[0019] A second aspect of the present invention provides a method for preparing a composite positive electrode material, comprising the following steps:

[0020] Step 1: Dispersing carbon-coated lithium manganese iron phosphate, a dispersant and an M salt in deionized water according to the designed ratio to obtain a mixed solution; wherein the M salt is any one or more of a soluble nickel salt, a soluble cobalt salt or a soluble iron salt;

[0021] Step 2: adding a coprecipitant to the mixed solution, and performing coprecipitation in a weakly alkaline environment to obtain a first precursor;

[0022] Step 3: In an inert atmosphere, the first precursor and the lithium source are mixed evenly, and dried to obtain a second precursor; the second precursor is calcined at 600° C.-900° C. to obtain a core material;

[0023] Step 4: Evenly mix the core material, lithium iron manganese phosphate and a coupling agent, and fuse and coat them in an inert atmosphere to obtain a composite positive electrode material.

[0024] The present invention first uses carbon-coated lithium iron manganese phosphate as a dopant and a deposition core to form a lithium-rich manganese-based material precursor solution with an M salt solution, and forms a carbon-coated lithium iron manganese phosphate doped lithium-rich manganese-based material after coprecipitation, drying and calcination; and then further solid-state mixing is performed by lithium iron manganese phosphate and a coupling agent to form a dense coating layer on the surface of the carbon-coated lithium iron manganese phosphate doped lithium-rich manganese-based material, and the coating layer effectively blocks the contact between the lithium-rich manganese-based material and the electrolyte, avoiding the catalytic decomposition of the electrolyte by the traditional lithium-rich manganese-based material. The composite positive electrode material provided by the present invention has a simple structure, a simple preparation process, and a low cost, and effectively solves the problems of complex structure, long process flow, and high preparation cost of the improved lithium-rich manganese-based material in the prior art.

[0025] Preferably, in step 1, the dispersant is anhydrous ethanol or n-butanol; the mass percentage of the dispersant in the mixed solution is 0.1%-0.3%.

[0026] Preferably, in step 1, the concentration of M salt in the mixed solution is 0.1 mol / L-3 mol / L.

[0027] Preferably, in step 2, the coprecipitant is a 0.1 mol / L-3 mol / L lithium hydroxide solution.

[0028] Preferably, in step 2, the pH of the weakly alkaline environment is 7.5-9.

[0029] Further preferably, in step 2, the weakly alkaline environment is adjusted using a 0.1 mol / L-3 mol / L ammonia solution.

[0030] Preferably, in step 2, the co-precipitation temperature is 20°C-30°C, and the co-precipitation treatment time is 8h-12h.

[0031] Preferably, in step three, the lithium source is lithium hydroxide.

[0032] Preferably, in step three, the calcination time is 3h-5h.

[0033] Preferably, in step three, the temperature is increased to 600°C-900°C at a rate of 5°C / min-10°C / min.

[0034] Preferably, in step three, the drying is carried out by spray drying, the inlet temperature of the spray drying is 250°C-350°C, the outlet temperature is 90°C-110°C, the pressure is 0.4MPa-0.5MPa, and the spray drying time is 10s-20s.

[0035] Preferably, in step 4, the coupling agent is methylsilane; the mass ratio of the added amount of the coupling agent to the lithium manganese iron phosphate is 0.08:1-0.1:1.

[0036] Preferably, in step four, a fusion coating machine is used for the fusion coating; wherein the line speed of the fusion coating machine is 0.4m / s-0.6m / s.

[0037] The third aspect of the present invention provides the use of the composite positive electrode material or the composite positive electrode material prepared by the preparation method of the composite positive electrode material in a lithium ion battery.

[0038] In summary, the composite positive electrode material provided by the present invention has a core-shell structure, which is composed of carbon-coated lithium iron manganese phosphate doped with lithium-rich manganese-based materials as the core, and lithium iron manganese phosphate as the coating layer material. The present invention adopts carbon-coated lithium iron manganese phosphate with higher safety as a dopant, which effectively improves the discharge specific capacity and cycle stability of the lithium-rich manganese-based material; and then lithium iron manganese phosphate is used as a coating layer material coated on the surface of the core material to block the contact between the lithium-rich manganese-based material and the electrolyte, inhibiting the lithium-rich manganese-based material from promoting the catalytic decomposition of the electrolyte, and greatly improving the safety performance of the composite positive electrode material. In addition, the composite positive electrode material of the present invention has a simple structure, a short process flow for preparing the composite positive electrode material, and a low preparation cost. The technical solution of the present invention effectively solves the problems in the prior art that the lithium-rich manganese-based material catalytically decomposes the electrolyte, causing rapid attenuation of battery performance, potential safety hazards, and the improved composite lithium-rich manganese-based material has a complex structure, a long process and high cost, and provides a new idea for the research of positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The composite positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 TEM image of O2 / LiMnFePO4;

[0040] Figure 2 This is a discharge performance test diagram of the composite positive electrode material described in Examples 1-3. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] The preparation method of carbon-coated lithium manganese iron phosphate used in each embodiment includes the following steps:

[0043] S1. Immerse 10 g of lithium manganese iron phosphate in 40 mL of saturated glucose solution, separate the solid and liquid, and vacuum dry at 60° C. and 0.7 MPa for 1 h to obtain a pretreated sample;

[0044] S2. In an inert atmosphere, the pretreated sample is heated to 600° C. at a heating rate of 10° C. / min and sintered for 3 h to obtain the carbon-coated lithium manganese iron phosphate.

[0045] Example 1

[0046] This embodiment provides a composite positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 / LiMnFePO4, specifically including the following:

[0047] The composite positive electrode material is a core-shell structure, including a core and a coating layer coated on the surface of the core; wherein the core is carbon-coated lithium manganese iron phosphate doped Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2; the coating layer is lithium manganese iron phosphate.

[0048] The preparation method of the composite positive electrode material is as follows:

[0049] Step 1: According to the designed ratio, 1.2 g of carbon-coated lithium manganese iron phosphate with a particle size of 0.5 μm, 0.24 g of n-butanol, 14.46 g of NiSO4·6H2O and 15.43 g of CoSO4·7H2O are dispersed in 70 mL of deionized water to obtain a mixed solution;

[0050] Step 2: Add 35 mL of 3 mol / L ammonia solution and 100 mL of 2 mol / L lithium hydroxide solution to the mixed solution, and perform coprecipitation for 10 h in a weakly alkaline environment at pH 8 to obtain a first precursor;

[0051] Step 3: Under an inert atmosphere, the first precursor was mixed evenly with 11.98 g of lithium hydroxide solid, and sent to a spray dryer. The inlet temperature was set to 300 ° C, the outlet temperature was set to 100 ° C, and the pressure was set to 0.4 MPa. The spray was dried for 10 seconds to obtain a second precursor; the second precursor was heated to 720 ° C at a heating rate of 8 ° C / min and calcined for 4 hours to obtain 44.13 g of core material;

[0052] Step 4: The core material is mixed evenly with 1.3 g of lithium manganese iron phosphate and 0.1 g of methylsilane, and the mixture is sent to a fusion coating machine for fusion coating at a linear speed of 0.5 m / s in an inert atmosphere to obtain a composite positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 / LiMnFePO4.

[0053] Example 2

[0054] This embodiment provides a composite positive electrode material Li 1.2 Mn 0.5 Ni 0.15 Co 0.15O2 / LiMnFePO4, specifically including the following:

[0055] The composite positive electrode material is a core-shell structure, including a core and a coating layer coated on the surface of the core; wherein the core is carbon-coated lithium manganese iron phosphate doped Li 1.2 Mn 0.5 Ni 0.15 Co 0.15 O2; the coating layer is lithium manganese iron phosphate.

[0056] The preparation method of the composite positive electrode material is as follows:

[0057] Step 1: According to the designed ratio, 1.3 g of carbon-coated lithium manganese iron phosphate with a particle size of 1.2 μm, 0.3 g of n-butanol, 20.5 g of NiSO4·6H2O and 19.85 g of CoSO4·7H2O are dispersed in 90 mL of deionized water to obtain a mixed solution;

[0058] Step 2: Add 40 mL of 1 mol / L ammonia solution and 150 mL of 2.2 mol / L lithium hydroxide solution to the mixed solution, carry out complex precipitation reaction at a weak alkaline environment of pH 8.2 for 10 h, filter, and obtain a first precursor;

[0059] Step 3: Under an inert atmosphere, the first precursor was mixed evenly with 13.5 g of lithium hydroxide solid, and sent into a spray dryer. The inlet temperature was set to 280 ° C, the outlet temperature was set to 110 ° C, and the pressure was set to 0.4 MPa. The spray drying was performed for 20 seconds to obtain a second precursor; the second precursor was heated to 750 ° C at a heating rate of 10 ° C / min and calcined for 4 hours to obtain 43.79 g of core material;

[0060] Step 4: The core material is mixed evenly with 1.8 g of lithium manganese iron phosphate and 0.15 g of methylsilane, and the mixture is sent to a fusion coating machine for fusion coating at a linear speed of 0.6 m / s in an inert atmosphere to obtain a composite positive electrode material Li 1.2 Mn 0.5 Ni 0.15 Co 0.15 O2 / LiMnFePO4.

[0061] Example 3

[0062] This embodiment provides a composite positive electrode material Li 1.2 Mn 0.6 Ni 0.2 O2 / LiMnFePO4, specifically including the following:

[0063] The composite positive electrode material is a core-shell structure, including a core and a coating layer coated on the surface of the core; wherein the core is carbon-coated lithium manganese iron phosphate doped Li 1.2 Mn 0.6 Ni 0.2 O2; the coating layer is lithium manganese iron phosphate.

[0064] The preparation method of the composite positive electrode material is as follows:

[0065] Step 1: According to the designed ratio, 1.3 g of carbon-coated lithium manganese iron phosphate with a particle size of 1.0 μm, 0.3 g of n-butanol and 27.85 g of NiSO4·6H2O are dispersed in 80 mL of deionized water to obtain a mixed solution;

[0066] Step 2: Add 40 mL of 1.5 mol / L ammonia solution and 145 mL of 1.5 mol / L lithium hydroxide solution to the mixed solution, carry out complex precipitation reaction at a weak alkaline environment of pH 7.9 for 10 h, filter, and obtain a first precursor;

[0067] Step 3: Under an inert atmosphere, the first precursor was mixed evenly with 14.85 g of lithium hydroxide solid, and sent to a spray dryer. The inlet temperature was set to 270 ° C, the outlet temperature was set to 100 ° C, and the pressure was set to 0.5 MPa. The spray drying was performed for 10 seconds to obtain a second precursor; the second precursor was heated to 780 ° C at a heating rate of 10 ° C / min and calcined for 4 hours to obtain 43.56 g of core material;

[0068] Step 4: The core material is mixed evenly with 2.1 g of lithium manganese iron phosphate and 0.18 g of methylsilane, and the mixture is sent to a fusion coating machine for fusion coating at a linear speed of 0.5 m / s in an inert atmosphere to obtain a composite positive electrode material Li 1.2 Mn 0.6 Ni 0.2 O2 / LiMnFePO4.

[0069] Example 4

[0070] This embodiment provides a composite positive electrode material Li 1.2 Mn 0.5 Co 0.3 O2 / LiMnFePO4, specifically including the following:

[0071] The composite positive electrode material is a core-shell structure, including a core and a coating layer coated on the surface of the core; wherein the core is carbon-coated lithium manganese iron phosphate doped Li 1.2 Mn 0.5 Co 0.3 O2; the coating layer is lithium manganese iron phosphate.

[0072] The preparation method of the composite positive electrode material is as follows:

[0073] Step 1: According to the designed ratio, 1.2 g of carbon-coated lithium manganese iron phosphate with a particle size of 1.2 μm, 0.3 g of n-butanol and 35.67 g of CoSO4·7H2O are dispersed in 90 mL of deionized water to obtain a mixed solution;

[0074] Step 2: Add 35 mL of 2 mol / L ammonia solution and 170 mL of 1.5 mol / L lithium hydroxide solution to the mixed solution, carry out complex precipitation reaction at a weak alkaline environment of pH 7.9 for 10 h, filter, and obtain a first precursor;

[0075] Step 3: Under an inert atmosphere, the first precursor was mixed evenly with 12.15 g of lithium hydroxide solid, and sent to a spray dryer. The inlet temperature was set to 320 ° C, the outlet temperature was set to 90 ° C, and the pressure was set to 0.5 MPa. The spray drying was performed for 20 seconds to obtain a second precursor; the second precursor was heated to 780 ° C at a heating rate of 10 ° C / min and calcined for 4 hours to obtain 41.09 g of core material;

[0076] Step 4: The core material is mixed evenly with 2.0 g of lithium manganese iron phosphate and 0.2 g of methylsilane, and the mixture is sent to a fusion coating machine for fusion coating at a linear speed of 0.5 m / s in an inert atmosphere to obtain a composite positive electrode material Li 1.2 Mn 0.5 Co 0.3 O2 / LiMnFePO4.

[0077] Comparative Example 1

[0078] This embodiment provides a composite positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 / LiMnFePO4, which is different from Example 1 in that there is no doping of carbon-coated lithium manganese iron phosphate, specifically including the following contents:

[0079] The composite positive electrode material is a core-shell structure, including a core and a coating layer coated on the surface of the core; wherein the core is Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2; the coating layer is lithium manganese iron phosphate.

[0080] The preparation method of the composite positive electrode material is as follows:

[0081] Step 1: 14.46 g NiSO4·6H2O and 15.43 g CoSO4·7H2O are dispersed in 70 mL deionized water to obtain a mixed solution;

[0082] Step 2: Add 35 mL of 3 mol / L ammonia solution and 100 mL of 2 mol / L lithium hydroxide solution to the mixed solution, and perform coprecipitation for 10 h in a weakly alkaline environment at pH 8 to obtain a first precursor;

[0083] Step 3: Under an inert atmosphere, the first precursor was mixed evenly with 11.98 g of lithium hydroxide solid, and sent to a spray dryer. The inlet temperature was set to 300 ° C, the outlet temperature was set to 100 ° C, and the pressure was set to 0.4 MPa. The spray drying was performed for 10 seconds to obtain a second precursor; the second precursor was heated to 720 ° C at a heating rate of 8 ° C / min and calcined for 4 hours to obtain 42.19 g of core material;

[0084] Step 4: The core material is mixed evenly with 1.3 g of lithium manganese iron phosphate and 0.1 g of methylsilane, and the mixture is sent to a fusion coating machine for fusion coating at a linear speed of 0.5 m / s in an inert atmosphere to obtain a composite positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 / LiMnFePO4.

[0085] In order to further demonstrate the technical effect of the present invention, the present invention conducted application performance tests on the composite positive electrode materials obtained in Examples 1-4 and Comparative Example 1, and prepared each composite positive electrode material into a button-type battery. The specific production steps are as shown in the test example.

[0086] Test example

[0087] S1. Evenly mix 0.08 g of the composite positive electrode material, 0.01 g of acetylene black, 0.01 g of polyvinylidene fluoride and 2 mL of N-methylpyrrolidone to obtain a positive electrode slurry;

[0088] S2. The positive electrode slurry is coated on aluminum foil to prepare a positive electrode sheet, and in an inert atmosphere, graphite is used as a negative electrode sheet to assemble a button cell.

[0089] The present invention conducted a rate test on the button cell obtained in the test example. The rate test was conducted using a LAND test instrument. The charge and discharge voltage was 2.5V-4.5V and the current was 0.2mAh. The first cycle was tested at a rate of 0.2C, and then a cyclic discharge test was conducted at a rate of 1C. The unit is mAh / g. The test results are shown in Table 1 and Figure 2 shown.

[0090] Table 1 Electrochemical performance test results of button cells prepared using the composite positive electrode materials obtained in various embodiments and comparative examples

[0091]

[0092] according to Figure 2 As can be seen from Table 1, the button cells prepared using the composite positive electrode materials obtained in Examples 1-3 have excellent performance, especially Example 1, which has a first-cycle discharge capacity of up to 302.1 mAh / g, an initial coulomb of up to 88.65%, a 0.2C discharge capacity of up to 299 mAh / g, and a 1C discharge capacity of 191 mAh / g after 100 cycles.

[0093] The present invention also conducted a transmission electron microscope scanning test on the composite positive electrode material obtained in Example 1, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the surface of the material is smooth and complete, and lithium manganese iron phosphate is coated on the surface of the core particles to form a core-shell structure.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite positive electrode material, characterized in that: The composite positive electrode material is a core-shell structure, including a core and a coating layer coated on the surface of the core; wherein the core is a carbon-coated lithium iron manganese phosphate-doped lithium-rich manganese-based material; and the coating layer is lithium iron manganese phosphate; The preparation method of the composite positive electrode material comprises the following steps: Step 1: Dispersing carbon-coated lithium manganese iron phosphate, a dispersant and an M salt in deionized water according to the designed ratio to obtain a mixed solution; wherein the M salt is any one or more of a soluble nickel salt, a soluble cobalt salt or a soluble iron salt; Step 2: adding a coprecipitant to the mixed solution, and performing coprecipitation in a weakly alkaline environment to obtain a first precursor; Step 3: In an inert atmosphere, the first precursor and the lithium source are mixed evenly, and dried to obtain a second precursor; the second precursor is calcined at 600° C.-900° C. to obtain a core material; Step 4: Evenly mix the core material, lithium iron manganese phosphate and a coupling agent, and fuse and coat them in an inert atmosphere to obtain a composite positive electrode material.

2. The composite positive electrode material according to claim 1, characterized in that: The composite positive electrode material comprises the following components in percentage by mass: 1%-3% of carbon-coated lithium manganese iron phosphate, 0.5%-5% of lithium manganese iron phosphate and the remainder of lithium-rich manganese-based material.

3. The composite positive electrode material according to claim 1 or 2, characterized in that: The particle size of the carbon-coated lithium manganese iron phosphate is 0.2 μm-1.2 μm; and / or The chemical formula of the lithium-rich manganese-based material is Li a Mn b M c O2, wherein a+b+c=2, 1<a≤1.2, 0.5<b≤0.6, 0.1<c≤0.3; M is any one or more of Ni, Co or Fe.

4. The method for preparing a composite positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: Step 1: Dispersing carbon-coated lithium manganese iron phosphate, a dispersant and an M salt in deionized water according to the designed ratio to obtain a mixed solution; wherein the M salt is any one or more of a soluble nickel salt, a soluble cobalt salt or a soluble iron salt; Step 2: adding a coprecipitant to the mixed solution, and performing coprecipitation in a weakly alkaline environment to obtain a first precursor; Step 3: In an inert atmosphere, the first precursor and the lithium source are mixed evenly, and dried to obtain a second precursor; the second precursor is calcined at 600° C.-900° C. to obtain a core material; Step 4: Evenly mix the core material, lithium iron manganese phosphate and a coupling agent, and fuse and coat them in an inert atmosphere to obtain a composite positive electrode material.

5. The method for preparing the composite positive electrode material according to claim 4, characterized in that: In step 1, the dispersant is anhydrous ethanol or n-butanol; the mass percentage of the dispersant in the mixed solution is 0.1%-0.3%; and / or In step 1, the concentration of M salt in the mixed solution is 0.1 mol / L-3 mol / L.

6. The method for preparing the composite positive electrode material according to claim 4, characterized in that: In step 2, the coprecipitant is a 0.1 mol / L-3 mol / L lithium hydroxide solution; and / or In step 2, the pH of the weakly alkaline environment is 7.5-9; and / or In step 2, the co-precipitation temperature is 20°C-30°C, and the co-precipitation treatment time is 8h-12h.

7. The method for preparing a composite positive electrode material according to claim 4, characterized in that: In step 3, the lithium source is lithium hydroxide; and / or In step 3, the calcination time is 3h-5h; and / or In step three, the temperature is increased to 600°C-900°C at a rate of 5°C / min-10°C / min.

8. The method for preparing a composite positive electrode material according to claim 4, characterized in that: In step 4, the coupling agent is methylsilane; the mass ratio of the added amount of the coupling agent to the lithium manganese iron phosphate is 0.08:1-0.1:

1.

9. Use of the composite positive electrode material according to any one of claims 1 to 3 or the composite positive electrode material prepared by the preparation method of the composite positive electrode material according to any one of claims 4 to 8 in a lithium ion battery.

Citation Information

Patent Citations

  • Preparation method of lithium manganese phosphate-coated lithium-rich manganese-based cathode material and lithium battery

    CN108630927A

  • Composite cathode material and preparation method thereof

    CN110459749A